Search for supersymmetry in final states with missing transverse momentum and three or more b-jets in 139 fb$$^{-1}$$ -1 of proton-proton collisions at $$\sqrt{s} = 13$$ s=13 TeV with the ATLAS detector. (Tufts University. Tisch Library., 2023)
Springer Open.